Exploring Global Impact: The Influence of Social Presence and Online Tutoring in Cultivating a Healthy Social Media Environment - Isriyah, Mudafiatun; Degeng, I Nyoman Sudana; Lasan, Blasius Boli; Muslihati, Muslihati (Bulletin of Counseling and Psychotherapy, 2024)
In the rapidly evolving landscape of digital communication, this research delves into the influential factors shaping a healthy social media environment. Focused on the interplay of social presence and online mentoring, the study investigates their collective impact on fostering positive online interactions. Utilizing a multi-method approach, data will be collected from diverse cultural contexts to offer a comprehensive understanding of the global dynamics at play. The research aims to identify the role of social presence in creating a sense of community and connectedness in the online sphere. Simultaneously, the study explores the potential of online mentoring as a catalyst for knowledge exchange and skill development, contributing to a more constructive digital discourse. The research methodology involves a combination of surveys, interviews, and content analysis across various social media platforms. The findings are expected to shed light on how the synergy between social presence and online mentoring can contribute to the creation of a healthy digital space that encourages collaboration, learning, and positive social engagement. This study not only contributes to the theoretical understanding of online dynamics but also provides practical insights for educators, mentors, and platform developers seeking to enhance the well-being of social media users on a global scale. The ultimate goal is to offer evidence-based recommendations for cultivating a positive and supportive online environment that transcends geographical and cultural boundaries.